Coating material for metal batteries
Patent Information
- Application Number
- CN202580025795.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-02
- Filing Date
- 2025-03-03
- Publication Date
- 2026-10-30
AI Technical Summary
然而,气态物质在袋状电芯中形成后的释放对于此类电池的大规模生产可能不是一种选择,因为它会减缓生产速度并增加生产成本
Smart Images

Figure CN123023153A_ABST
Abstract
Description
Technical Field
[0001] This invention generally relates to electrochemical cells that convert chemical energy into electrical energy, and battery packs or modules comprising two or more of these electrochemical cells, wherein each electrochemical cell is formed as a pouch cell, a cylindrical cell, or a prismatic cell. The electrochemical cell and / or battery pack or module includes a coating material on one or more surfaces within the pouch cell, cylindrical cell, or prismatic cell that are in contact with an electrolyte, such that the coating material is configured to reduce gas generation in the electrolyte. Background Technology
[0002] The statements in this section provide only background information in connection with this disclosure and may not constitute prior art.
[0003] Metal-ion batteries and metal batteries both utilize soluble metal ions as transport ions within the battery to enable electrochemical reactions for energy storage and release. The primary difference between metal-ion batteries and metal batteries lies in the choice of anode active material. When the anode active material is graphite, carbon, silicon, antimony, or a similar material (different from the metal that provides the metal ions for energy storage / release), the battery is considered a metal-ion battery. Several examples of metal-ion batteries include lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, magnesium-ion batteries, calcium-ion batteries, and aluminum-ion batteries. In contrast, metal batteries utilize the corresponding metal that forms the metal ions as the active anode material. Several examples of metal batteries include lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, magnesium-ion batteries, calcium-ion batteries, and aluminum metal batteries.
[0004] In metal-ion batteries and metal batteries, metal ions typically insert into the anode side of the battery cell and extract from the cathode side during charging. During discharging, the metal ions are released from the anode side of the cell and migrate back to the cathode side. These batteries often contain organic electrolytes to improve their energy density due to the high voltage stability of organic solvents. Among these batteries, lithium-ion batteries have achieved widespread commercial success.
[0005] Lithium-ion batteries are widely used in a variety of applications, such as portable electronics, electric vehicles, and grid storage, due to their long cycle life and high energy or power density. The use of lithium-ion batteries in electric vehicles (EVs) offers the potential to reduce global greenhouse gas emissions and air pollution. State-of-the-art battery chemistry is typically based on lithium-ion technology; for example, the cathode contains LiNiMnCoO2 (NMC), LiNiCoAlO2 (NCA), LiMn2O4 (LMO), LiFePO4 (LFP), or LiCoO2 (LCO); the anode is formed from graphite or carbonaceous materials; the electrolyte mixture contains a combination of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and lithium salts such as LiPF6; and a permeable Li2O3 electrolyte lies between the cathode and anode. + Inorganic or polymer separators for ion migration. Battery cells are typically encapsulated in sealed laminated foil (i.e., pouch cells) or in metal casings (i.e., cylindrical or prismatic cells).
[0006] The use of polar organic electrolytes makes the performance of metal and metal-ion batteries highly susceptible to moisture contamination. The presence of gaseous substances can stem from the decomposition of residual moisture in the electrolyte, anode, and cathode, as well as the electrochemical decomposition of carbonate electrolytes. For lithium-ion batteries, the situation is considered even worse because LiPF6 salts are highly reactive with water. Small amounts of moisture or water may remain in the battery during manufacturing, even after thorough drying. When LiPF6 salts react with water, they generate HF and other decomposition products, potentially releasing gaseous substances inside the battery.
[0007] When lithium-ion batteries need to operate at high voltages and / or high temperatures, the severity of gas escape from the battery is rapidly amplified because the electrochemical reactions that produce gases and other byproducts accelerate the degradation and aging of the cell. Furthermore, when gaseous substances form and accumulate within the cell, the pressurized gaseous substances can cause the cell to expand and rupture, leading to safety issues.
[0008] Thermal runaway is a self-accelerating exothermic reaction occurring inside a battery cell, which can be triggered by hot spots within the cell (e.g., short circuits) or by external heat sources (e.g., electrical faults). Thermal runaway leads to a violent reaction within the cell, producing large quantities of hot, toxic, and flammable gases that may be released from the cell, and hot particles may also be ejected. The released gases and particles can pose serious safety and health risks, such as fire, explosion, and the formation of toxic atmospheres. The main gaseous compounds produced by thermal runaway reactions include carbon dioxide (CO2), carbon monoxide (CO), hydrogen (H2), and various hydrocarbon gases. Except for CO2 and H2O, all gases produced by thermal runaway are inherently flammable and / or explosive. The suppression effect of present inert gases or vapors (such as CO2 and water vapor) cannot prevent the ignition of flammable gas mixtures during thermal runaway.
[0009] In lithium-ion batteries, porous polymer separators can be coated with boehmite or alumina to enhance safety during thermal runaway events. Boehmite (AlOOH) is preferred over alumina (Al₂O₃) because it represents a softer and cheaper material. However, using boehmite in batteries may generate significantly more gaseous matter than using Al₂O₃, due to the relatively high moisture content and / or presence of -OH functional groups associated with boehmite.
[0010] The presence of gaseous substances within battery cells can be mitigated by releasing them immediately after their formation in pouch cells. However, releasing gaseous substances after their formation in pouch cells may not be an option for the large-scale production of such batteries, as it would slow down production and increase costs. For cylindrical and prismatic cells, releasing the gas after its formation would be difficult. Avoiding the gas release step during battery cell production would be preferable. Therefore, it is necessary to reduce the amount of gas generated by the use of boehmite and other metal oxides and / or metal hydroxides in battery cells. Summary of the Invention
[0011] This disclosure generally relates to electrochemical cells for converting chemical energy into electrical energy and battery packs incorporating two or more of these electrochemical cells. The electrochemical cells can be formed as pouch cells, cylindrical cells, or prismatic cells. Each electrochemical cell includes a coating material on one or more surfaces within the pouch, cylindrical, or prismatic cell that are in contact with an electrolyte. The coating material comprises a metal oxide and / or a metal hydroxide and a metal phosphate, such that the coating material is configured to reduce the amount of gas present inside the electrochemical cell. Where desired, the metal oxide or metal hydroxide may be boehmite, and the metal phosphate may be aluminum phosphate.
[0012] According to one aspect of this disclosure, the coating material may be located on the surface of a spacer or current collector. The coating material comprises a homogeneous mixture of the metal oxide and / or metal hydroxide with the metal phosphate, or exists as a composite structure comprising the metal oxide and / or metal hydroxide in a first layer and the metal phosphate in a second layer. The first layer typically comprises a first side and a second side, wherein the first side is in direct contact with one or more surfaces within the pouch cell, cylindrical cell, or prismatic cell, and the second layer is in direct contact with the second side of the first layer. Where desired, the homogeneous mixture may be located within a single coating or within multiple coatings.
[0013] According to another aspect of this disclosure, the electrochemical cell can be a metal battery or a metal-ion battery. The metal battery or metal-ion battery typically incorporates one or more metals selected from lithium, sodium, potassium, magnesium, calcium, or aluminum. When necessary, the electrochemical cell can be a lithium battery or a lithium-ion battery.
[0014] In the coating material, the metal oxide or metal hydroxide may include alumina, alumina hydroxyacid with the chemical formula AlOOH, zeolite, titanate, zirconate, aluminate, or mixtures or derivatives thereof. The zeolite may include structures described as FAU, LTA, CHA, BEA, or ZSM-5. The metal phosphate may include amorphous aluminum phosphate, crystalline aluminum phosphate, aluminum phosphate molecular sieves, or mixtures thereof. The metal phosphate typically comprises a metal selected from the group consisting of Li, Mg, Ca, Sr, Ba, Ti, Zr, and mixtures thereof.
[0015] The metal oxide or metal hydroxide and the metal phosphate may be included in the coating material in a mass ratio of 99:1 to 1:99. Alternatively, the metal oxide or metal hydroxide and the metal phosphate may be included in the coating material in a mass ratio of 90:10 to 10:90. Alternatively, the coating material comprises the metal oxide or metal hydroxide and the metal phosphate in a mass ratio of 75:25 to 25:75.
[0016] The metal oxide or metal hydroxide may be included in the coating material at a mass percentage of 99% to 25%, and the metal phosphate may be included in the coating material at a mass percentage of 1% to 75%. Alternatively, the metal oxide or metal hydroxide may be present at a mass percentage of 98% to 50%, and the metal phosphate may be present at a mass percentage of 2% to 50%. Alternatively, the coating material may comprise 95% to 75% by mass of the metal oxide or metal hydroxide and 5% to 25% by mass of the metal phosphate, relative to the total mass of the coating material.
[0017] According to another aspect of this disclosure, the coating material further comprises, with a mass percentage of 1% to 20%, a polymeric binder relative to the total mass of the coating material.
[0018] According to another aspect of this disclosure, a battery pack or module is provided comprising two or more electrochemical cells connected in series or in parallel with each other as described above and further defined herein.
[0019] According to another aspect of this disclosure, a method is provided for preparing an electrochemical cell formed as described above and further defined herein as a pouch cell, a cylindrical cell, or a prismatic cell. The method generally includes the following steps: 1) providing components for the electrochemical cell, including an anode, a cathode, a separator, an electrolyte, and a housing in the form of a pouch, a cylindrical, or a prismatic package; 2) providing a coating material comprising a metal oxide and / or a metal hydroxide and a metal phosphate, such that the coating material is configured to reduce the amount of gas inside the cell; 3) applying the coating material to one or more surfaces located within the electrochemical cell that are in contact with the electrolyte; and 4) assembling the components of the electrochemical cell to form a pouch cell, a cylindrical cell, or a prismatic cell.
[0020] Other applicable scope will become apparent from the description provided herein. It should be understood that the description and specific examples are for illustrative purposes only and are not intended to limit the scope of this disclosure. Attached Figure Description
[0021] To better understand this disclosure, various forms thereof will now be described by way of example, with reference to the accompanying drawings. Elements in each drawing are not necessarily drawn to scale, but rather the focus is on illustrating the principles of the invention.
[0022] Figure 1A This is a schematic diagram of an electrochemical cell in the form of a pouch cell.
[0023] Figure 1BThis is a schematic diagram of an electrochemical battery cell in the form of a cylindrical battery cell.
[0024] Figure 1C This is a schematic diagram of an electrochemical battery cell in the form of a prismatic battery cell.
[0025] Figure 2 This is a schematic diagram of an electric vehicle having a battery pack or module containing multiple electrochemical cells.
[0026] Figure 3A It is a cross-section of a coating material applied to the surface of a component in an electrochemical cell in accordance with the teachings of this disclosure.
[0027] Figure 3B It is a cross-section of another coating material applied to the surface of a component in an electrochemical cell in accordance with the teachings of this disclosure.
[0028] Figure 3C It is a cross-section of another coating material applied to the surface of a component in an electrochemical cell in accordance with the teachings of this disclosure.
[0029] Figure 4 The graphic representation is attributed to the gas produced by the addition of water and boehmite to the electrolyte.
[0030] Figure 5A This is a comparison of X-ray diffraction (XRD) patterns of boehmite (i.e., γ-AlO(OH)) measured before and after aging in an electrolyte.
[0031] Figure 5B This is a graphical comparison of the mass loss (%) of boehmite (i.e., γ-AlO(OH)) before and after aging in the electrolyte as a function of temperature, as measured by thermogravimetric analysis (TGA).
[0032] Figure 6A This is a comparison of X-ray diffraction (XRD) patterns of aluminum phosphate (AlPO4) measured before and after aging in an electrolyte.
[0033] Figure 6B This is a graphical comparison of the mass loss (%) of aluminum phosphate (AlPO4) in the electrolyte before and after aging as a function of temperature, as measured by thermogravimetric analysis (TGA).
[0034] Figure 7 It is a flowchart describing the steps associated with a method for forming an electrochemical cell according to the teachings of this disclosure.
[0035] Figure 8 It is a flowchart describing the steps associated with a method for forming a battery pack or module according to the teachings of this disclosure.
[0036] The accompanying drawings described herein are for illustrative purposes only and are not intended to limit the scope of this disclosure in any way. Detailed Implementation
[0037] The following description is exemplary in nature only and is in no way intended to limit this disclosure or its application or use. For example, electrochemical cells formed and used in accordance with the teachings contained herein are described throughout this disclosure in conjunction with battery packs or modules for electric vehicles in order to more fully illustrate their structural elements and uses. The incorporation and use of such electrochemical cells in other applications (including, but not limited to, any application where the generation of gas or vapor may be a problem) is considered to be within the scope of this disclosure. It should be understood that throughout the description and drawings, corresponding reference numerals denote the same or corresponding parts and features.
[0038] For the purposes of this disclosure, the terms “about” and “substantially” are used herein in relation to measurable values and ranges due to anticipated variations known to those skilled in the art (e.g., limitations and variability in measurements).
[0039] For the purposes of this disclosure, the terms "at least one" and "one or more" are used interchangeably and may have the same meaning. These terms refer to including a single element or multiple elements and may also be indicated by the suffix "(s)" at the end of the element. For example, "at least one metal oxide," "one or more metal oxides," and "metal oxide(s)" are used interchangeably and are intended to have the same meaning.
[0040] As used herein, “electrochemical cell” is considered similar to or the same as “battery cell”. For the purposes of this disclosure, “battery cell” refers to the basic electrochemical unit of a battery, which includes an anode and a cathode, and any components for converting stored chemical energy into electrical energy, such as electrodes, separators, and electrolytes. In contrast, “battery” refers to at least one battery cell housed within a casing (e.g., a pouch, cylindrical, or prismatic casing) and having electrical connections and possibly electronic devices for control and protection. “Battery pack” or “battery module” refers to a collection of more than one battery (in other words, multiple batteries) connected in series or parallel to each other to increase the resulting voltage or capacity, wherein the collection of batteries is fixed within a casing.
[0041] This disclosure generally describes electrochemical cells that convert chemical energy into electrical energy, and battery packs or modules comprising two or more electrochemical cells, wherein each electrochemical cell is formed as a pouch cell, a cylindrical cell, or a prismatic cell. The electrochemical cells, and thus the battery packs or modules incorporating such electrochemical cells, include a coating material on one or more surfaces within the pouch cell, cylindrical cell, or prismatic cell that are in contact with an electrolyte. The coating material typically comprises metal oxides and / or metal hydroxides with metal phosphates, such that the coating material is configured to reduce gas generation inside the battery.
[0042] According to one aspect of this disclosure, the electrochemical cell can be a metal battery or a metal-ion battery. The metal battery or metal-ion battery typically incorporates a type of soluble metal ion as a transport ion to enable electrochemical reactions for energy storage and release. The metal comprises one or more of lithium, sodium, potassium, magnesium, calcium, or aluminum; alternatively, the metal is lithium. When lithium is the selected metal, the electrochemical cell can be a lithium battery or a lithium-ion battery.
[0043] Referring now to Figure 1, various types of battery cells are shown in the form of pouch cell 1A, cylindrical cell 1B, and prismatic cell 1C. In each of these batteries, battery cells 1A, 1B, and 1C (including anode 3 (negative), separator 5, and cathode 7 (positive)) are shown encapsulated within a housing or casing 10. Both anode 3 and cathode 7 include a layer of active material to act as the respective electrode (+ / -) and a layer of metal (e.g., Al, Cu, Ni, Ti, etc.) to act as a current collector. An electrolyte (not shown) is typically present and in contact with both the anode and cathode, wherein ions migrate in the electrolyte through the separator located therebetween.
[0044] The electrochemical cell disclosed herein can be packaged as a pouch cell 1A, a cylindrical cell 1B, or a prismatic cell 1C. Alternatively, the electrochemical cell is packaged as a pouch cell 1A or a cylindrical cell 1B; alternatively, the electrochemical cell is packaged as a pouch cell 1A. Many consumer electronics and electric vehicles use pouch-shaped lithium-ion cells to provide efficient space utilization compared to cylindrical and prismatic cell designs. However, in pouch cells, replacing the metal containers used for cylindrical and prismatic cells with polymer encapsulation comes at a cost, as the pouch cell may expand due to gas generation, leading to leakage from the sealed area.
[0045] Cylindrical cells can also be used in many applications, including electric vehicles, when needed, due to their ease of manufacture, mechanical stability, and ability to withstand much higher internal pressures without deformation compared to pouch cells. However, these batteries can still deform and burst if the internal gas pressure becomes too high. Most cylindrical cells have safety features that prevent them from rupturing under high pressure, resulting in leakage and rendering them unusable. Therefore, minimizing gas generation is also desirable for cylindrical cells.
[0046] Prismatic cells can also be used in a variety of industrial applications and some powertrain systems in hybrid and electric vehicles. Prismatic cells use a cubic metal can, offering greater packaging flexibility and space efficiency than cylindrical cells. These cells have a certain tolerance to high internal pressure, typically falling between pouch cells and cylindrical cells.
[0047] Now for reference Figure 2 The diagram shows a battery pack or module 25 within an electric vehicle 30. Within this battery pack or module 25 are multiple electrochemical cells in the form of batteries (i.e., batteries 1A-C arranged in 2 rows × 5 columns). The batteries 1A-C can be held in place using a structural material 35 (e.g., foam). When needed, the battery pack or module 25 may also contain dielectric oil (not shown) flowing through it to provide additional cooling capacity as a means of thermal management.
[0048] According to one aspect of this disclosure, the presence of a metal phosphate (e.g., aluminum phosphate) in the coating can suppress the generation of gaseous substances in a moisture-contaminated electrolyte. Furthermore, the presence of this metal phosphate can also suppress the generation of gaseous substances generated by other coating materials (e.g., boehmite) used in the electrochemical cell. Boehmite coatings alone in an electrochemical cell generate a significant amount of gaseous substances.
[0049] Typically, the coating materials of this disclosure combine at least one type of metal phosphate with one or more types of metal oxides and / or metal hydroxides. The metal oxides and / or metal hydroxides in the coating materials offer a variety of benefits, including but not limited to cost and hardness. On the other hand, although the metal phosphates in the coating materials may be more expensive than the metal oxides and / or metal hydroxides, the metal phosphates offer the benefit of suppressing gas generation caused by the metal oxides and / or metal hydroxides. The combination of metal phosphates with metal oxides / hydroxides provides the coating materials of this disclosure with benefits associated with both metal phosphates and metal oxides / hydroxides.
[0050] In other words, the effectiveness of metal phosphates in suppressing gas generation caused by other coating components present in the electrochemical cell allows the coating materials of this disclosure to provide a variety of beneficial functions while minimizing the presence of gas generation. For example, when the coating materials of this disclosure contain boehmite and metal phosphates, the coating materials provide the benefits of low cost and flexibility without significant excessive gas generation. In another example, when the coating materials of this disclosure consist of zeolite and metal phosphates, the coating materials provide the benefits of zeolite in removing electrolyte impurities without excessive gas generation. The use of zeolite as a separator coating material is generally not commercially viable because zeolite can carry adhering moisture into the battery cell and generate significant amounts of gaseous substances. However, by introducing metal phosphates, the coating materials of this disclosure can also contain zeolite without the problem of gas generation.
[0051] Refer again Figure 1A , 1B In conjunction with 1C, coating material 17 may be applied to one or more surfaces located within the pouch cell 1A, cylindrical cell 1B, or prismatic cell 1C. Examples of such surfaces include, but are not limited to, the surfaces of the electrode layers or current collector layers in the anode 3 and / or cathode 7, and the surface of the spacer 5. Coating material 17 may be applied to one side or both sides of the spacer 5 without departing from the scope of this disclosure. Alternatively, coating material 17 may be applied as an edge coating to the current collector layers in the anode 3 and / or cathode 7. Alternatively, coating material 17 may be applied to the surface of the spacer 5. Coating material 17 may be applied to the entire surface or at least a portion of the surface.
[0052] Therefore, according to one aspect of this disclosure, a coated spacer is provided for forming an electrochemical cell as a pouch cell, cylindrical cell, or prismatic cell. The coated spacer typically comprises at least one layer of a porous polymer and at least one layer of a coating material comprising metal oxides and / or metal hydroxides and metal phosphates, such that the coating material is configured to reduce the amount of gas generated when the spacer is used inside the electrochemical cell together with an organic electrolyte.
[0053] Now for reference Figure 3A and 3B The coating material 17 can be applied as a homogeneous mixture of one or more metal oxides and / or metal hydroxides 23 with at least one type of metal phosphate 27 to one or more surfaces (e.g., spacers, etc.) of the electrochemical cell 20. The coating material 17 can be a single coating. Figure 3A ) or as multiple thinner coatings ( Figure 3B ( ) to apply, for example, one layer applied on top of another layer.
[0054] Now for reference Figure 3C The coating material 17 can also be applied as a composite structure to one or more surfaces 20 in the electrochemical cell. The composite structure comprises a metal oxide and / or metal hydroxide 23 in a first layer and a metal phosphate 27 in a second layer. The first layer typically comprises a first side 32 and a second side 34, the first side 32 being in direct contact with one or more surfaces 20 within the pouch cell, cylindrical cell, or prismatic cell, while the second layer is in direct contact with the second side 34 of the first layer.
[0055] The metal oxides or metal hydroxides introduced into the coating material may include alumina, alumina hydroxyacid with the chemical formula AlOOH, zeolites, titanates, zirconates, aluminates, or mixtures or derivatives thereof. Alternatively, the metal oxides and / or metal hydroxides may include, but are not limited to, one or more of MgO, CaO, SrO, BaO, TiO2, ZrO2, Al2O3, boehmite, zeolites, and / or their hydroxides, as well as their derivatives. Alternatively, the metal oxides and / or metal hydroxides include alumina, boehmite, zeolites, and mixtures thereof. Zeolites may include, but are not limited to, structures described as FAU, LTA, CHA, BEA, or ZSM-5. Alternatively, the metal oxide / hydroxide is boehmite.
[0056] Similar to boehmite, zeolites may contain significant amounts of moisture, which can be detrimental to the electrolyte and / or generate substantial amounts of gas during aging. Furthermore, several other metal oxides / hydroxides, such as alumina and titanates, also produce significant amounts of gas during aging. Each of these metal oxides / hydroxides would benefit from blending with metal phosphates in the coating material applied to the surface of the electrochemical cell to reduce the amount of gas generated by such oxides / hydroxides during operation and aging.
[0057] Metal phosphates can remove both HF and H₂O that may be present in the electrolyte used in electrochemical cells. Metal phosphates introduced together with metal oxides and / or metal hydroxides to form coating materials may include, but are not limited to, magnesium phosphate, zinc phosphate, copper phosphate, iron phosphate, cobalt phosphate, nickel phosphate, silver phosphate, titanium phosphate, zirconium phosphate, aluminum phosphate, lithium phosphate, barium phosphate, calcium phosphate, strontium phosphate, and combinations or mixtures thereof. Alternatively, the metal phosphate may comprise a metal selected from the group consisting of Mg, Ca, Sr, Ba, Ti, Zr, and mixtures thereof. Alternatively, the metal phosphate may be aluminum phosphate.
[0058] Throughout this disclosure, amorphous aluminum phosphate has been used as an example of a metal phosphate present in coating materials. However, the same gas generation suppression effect can be extended to aluminum phosphates with other structures, including crystalline aluminum phosphate and aluminum phosphate molecular sieves, without departing from the scope of this disclosure. Furthermore, other metal phosphates may also be used. Alternatively, the metal in the metal phosphate belongs to the alkaline earth metals (barium, calcium, magnesium, and strontium), transition metals (titanium, zirconium), and / or lithium families due to lower cost and stability when exposed to HF, which may be present in the electrolyte. Li3PO4 may be used alternatively, but it is less preferred than AlPO4 because lithium is much more expensive.
[0059] The mass ratio of metal oxides and / or metal hydroxides to metal phosphates in the coating material can range from 99:1 to 1:99; alternatively, 95:5 to 5:95; alternatively, 90:10 to 10:90; alternatively, 80:20 to 20:80; alternatively, 75:25 to 25:75; alternatively, 60:40 to 40:60. Alternatively, the mass ratio of metal oxides and / or hydroxides to metal phosphates in the coating material is approximately 50:50. Alternatively, the coating material can be described as containing 99% to 25% by mass of metal oxides or metal hydroxides and 1% to 75% by mass of metal phosphates relative to the total mass of the coating material. Alternatively, the coating material contains 98% to 50% by mass of metal oxides or metal hydroxides and 2% to 50% by mass of metal phosphates relative to the total mass of the coating material. Alternatively, the coating material comprises 95% to 75% by mass of metal oxides or metal hydroxides and 5% to 25% by mass of metal phosphates, relative to the total mass of the coating material.
[0060] The combined mass of metal oxides / hydroxides and metal phosphates present in the coating material can account for 100% by weight of the total weight of the coating material. Alternatively, the combined mass of metal oxides / hydroxides and metal phosphates relative to the total weight of the coating material can account for: ≥ 95% by weight; alternatively, ≥ 90% by weight; alternatively, at least 85% by weight; alternatively, ≥ 80% by weight; alternatively, 75% by weight or more.
[0061] When necessary, the coating material may contain additional additives, such as one or more adhesives or adhesion promoters. These additional additives may be present by weight, typically in the following amounts: up to 25% by weight; alternatively, ≤ 20% by weight; alternatively, ≤ 15% by weight; alternatively, ≤ 10% by weight; alternatively, ≤ 5% by weight. Alternatively, the coating material may contain 1% to 20% by weight of a polymeric adhesive relative to the total weight of the coating material. The adhesive may include, but is not limited to, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyvinylpyrrolidone (PVP), polypropylene oxide (PPO), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), sodium ammonium alginate (SAA), or mixtures thereof.
[0062] Any specific examples provided in this disclosure are for illustrating various embodiments of the invention and should not be construed as limiting the scope of this disclosure. The embodiments shown in this disclosure have been described in a manner that allows for a clear and concise description, but it is intended and should be understood that the embodiments can be combined or separated in various ways without departing from the invention. For example, it should be understood that all preferred features described herein apply to all aspects of the invention described herein.
[0063] Example Material Amorphous AlPO4 was prepared by dissolving Al(NO3)3·9H2O and H3PO4 (85 wt%) in water to form a solution with an Al to P molar ratio of approximately 1:1.1. Ammonia (approximately 28 wt%) was then added to the solution to raise the pH to approximately 8.5. The resulting white precipitate was collected by filtration and then washed with water. After drying the collected precipitate in an oven, the wet powder was heated in air at 750°C for 8 hours to form amorphous AlPO4.
[0064] Boehmite was prepared by a conventional hydrothermal method using gibbsite as a raw material.
[0065] Gas production researchThe powder to be tested (which includes metal oxides and / or metal hydroxides, metal phosphates, or mixtures of metal oxides / hydroxides and metal phosphates) is vacuum dried at 110°C for 10-12 hours, and then transferred to a glove box to minimize the presence of any moisture. A total of 12 grams of electrolyte (ethylene carbonate / ethyl methyl carbonate or EC / EMC (3 / 7) of 1M LiPF6, 1% vinyl chloride or VC, 2% fluoroethylene carbonate or FEC) is then sealed with or without 3.0 grams of the dried powder in a pouch bag. The volume of the sealed bag is determined by measuring its weight in air and water. The net difference in weight is considered to represent the bag volume. After volume measurement, the bag is stored in an oven preheated to 85°C for a predetermined or target time (i.e., 72 or 95 hours). After heating, the bag is cooled in air for >2 hours. The volume of the bag is measured again. The volume difference before and after heating represents the volume of gas generated during the aging process.
[0066] The gas generation rates measured during high-temperature aging of electrolytes with or without moisture and / or with or without metal oxides / hydroxides and / or metal phosphates are summarized in Table 1 below. High aging temperatures were used to accelerate the gas generation rate. A bag containing only dry electrolyte (Sample 1) showed no gas generation after aging at 85°C for 3 days. As shown in Sample 2, a significant amount of gas (approximately 0.4 ml) was generated upon the addition of a small amount of water (approximately 442 ppm). When the amount of water present increased to approximately 1542 ppm, the amount of gas generated also increased to approximately 1.9 ml (Sample 3). Therefore, the amount of gas generated during aging shows a direct correlation with the moisture content present in the electrolyte. This linear relationship is evident in… Figure 4 It is shown graphically in the middle.
[0067] Still refer to Table 1 and Figure 4 A total of 3 grams of boehmite was sealed in a bag along with dry electrolyte (Sample 9) and subjected to an aging process. After 3 days of aging, a total of 18.4 ml of gas was measured (Sample 9). If this amount of gas is due to water production, the measurement indicates that up to 25% water may have been released from the boehmite. One might expect that this relatively large amount of water could originate from the decomposition of AlOOH and the release of -OH groups. To determine whether this occurred, the X-ray diffraction (XRD) pattern of the boehmite before aging was compared with the XRD pattern of the boehmite after aging (Sample 9). Figure 5A As shown, the crystal structure of boehmite remained unchanged after aging at 85°C. Furthermore, a comparison of thermogravimetric analysis (TGA) results between unaged and aged boehmite (sample 9) was performed. Figure 5BThis indicates that the mass loss of boehmite was not altered by the aging process. Therefore, the crystal structure of boehmite remained unchanged during aging, and the material did not decompose. The large amount of gas generated during aging by adding boehmite (sample 9) to the electrolyte is believed to be due not only to the moisture introduced into the electrolyte by the boehmite, but also to the catalytic effect involved in the reaction between the boehmite and the electrolyte.
[0068] Table 1. Effects of moisture, boehmite, AlPO4 and their mixtures on electrolyte gas production
[0069] Referring again to Table 1, a total of 3 grams of amorphous AlPO4 was sealed together with dry electrolyte in a bag (Sample 4) and subjected to an aging process. After 3 days of aging, only 0.1 ml of gas was measured to have been produced (Sample 4). The X-ray diffraction (XRD) pattern of aluminum phosphate before aging was compared with the XRD pattern of aluminum phosphate after aging (Sample 4). Figure 6A The XRD comparison showed that the amorphous structure of the metal phosphate did not change after aging at 85°C.
[0070] However, a comparison of thermogravimetric analysis (TGA) of unaged aluminum phosphate and aged aluminum phosphate (sample 4) Figure 6B The results showed that AlPO4 exhibited significant weight loss during heating or aging. The aged metal phosphate was collected from the aging electrolyte after filtration, washed with isopropanol, and then dried in air at 120°C prior to TGA measurements. Therefore, most of the weight loss exhibited by the aged phosphate was not a result of the presence of any physically adsorbed moisture. The release of any adsorbed moisture is expected to occur at relatively low temperatures, such as below 300°C or even <200°C. Instead, it is believed that AlPO4 has reacted with the electrolyte and remained in solid or liquid form through chemical bonding or other attractive forces.
[0071] Referring again to Table 1, a total of 3 grams of amorphous AlPO4 and 6.1 mg (508 ppm) of water were sealed together with dry electrolyte in a bag (sample 5) and subjected to an aging process to examine the potential effect of metal phosphates on inhibiting gas generation. Based on Figure 4 The linear relationship shown in the figure is based on the expected amount of gas produced by the additional water added to sample 5. Figure 4 The linear relationship shown was estimated to be approximately 0.61 ml. However, the amount of gas produced was only 0.15 ml (sample 5). Therefore, this example demonstrates that AlPO4 can effectively suppress gas produced due to the presence of moisture.
[0072] Referring again to Table 1, multiple tests were conducted using boehmite as a mixture of metal oxide / hydroxide and AlPO4 as a metal phosphate. More specifically, AlPO4 was blended with boehmite in various mass ratios of 3 / 1, 1 / 1, and 1 / 3 (samples 6, 7, and 8), sealed with dry electrolyte, and subjected to an aging process. The gas volume measured after aging for samples 6, 7, and 8 ranged from 0.09 to 0.14 ml, significantly lower than the gas volume produced by boehmite (sample 9) and close to the gas volume measured for AlPO4 alone (sample 4).
[0073] One would expect the amount of gas produced to gradually decrease as the boehmite content decreased from 100% (Sample 9) to 75% (Sample 6), 50% (Sample 7), and 25% (Sample 8). In other words, if there were no synergistic effect between AlPO4 and boehmite, the gas production would be expected to decrease from 18.42 ml (100% boehmite) to 13.83 ml (75%), 9.25 ml (50%), and 4.68 ml (25%). However, surprisingly, the measured gas production decreased from 18.42 ml (100% boehmite, Sample 9) to 0.14 ml (75%, Sample 6), 0.09 ml (50%, Sample 7), and 0.14 ml (25%, Sample 8). This result indicates a synergistic interaction between boehmite and metal phosphates, and that AlPO4 effectively inhibits gas production from boehmite when metal phosphates are mixed with boehmite. It would be reasonable to assume that a higher or lower concentration of metal phosphates could also be used to reduce the amount of gas produced by boehmite.
[0074] The suppression of gas generation caused by boehmite in the presence of AlPO4 was consistent with the TGA measurements of AlPO4 before and after aging. Figure 6B Although not wanting to be strictly bound by theory, it is assumed that AlPO4 reacts with and / or captures gases produced or released by boehmite in the electrolyte. As a result, the amount of measurable gas generated from boehmite in the presence of AlPO4 is negligible (samples 6, 7, and 8).
[0075] Based on the results shown in Table 1 and as further described herein, metal phosphates (e.g., amorphous aluminum phosphate) can be blended with another metal oxide or metal hydroxide that contains high moisture content or generates large amounts of gas during aging to effectively suppress the release of such moisture or the generation of such gas. Therefore, applying such a mixture of metal oxide / hydroxide and metal phosphate as a coating material to the surface of an electrochemical cell will provide the benefit of reducing the generation of gaseous substances during the operation and aging of the electrochemical cell.
[0076] According to another aspect of this disclosure, a battery pack or module is provided. The battery pack or module typically comprises two or more electrochemical cells or battery cells formed according to the teachings of this disclosure and packaged as pouch cells, cylindrical cells, or prismatic cells. These two or more cells may be connected in series or in parallel with each other.
[0077] According to another aspect of this disclosure, a method is provided for preparing an electrochemical cell formed as a pouch cell, a cylindrical cell, or a prismatic cell. Reference is now made to... Figure 7 The method 100 typically includes the following steps: providing 105 for an assembly of an electrochemical cell; providing 110 a coating material comprising a metal oxide and / or a metal hydroxide and a metal phosphate, such that the coating material is configured to trap gases present in the electrolyte; applying 115 the coating material to one or more surfaces located within the electrochemical cell in contact with the electrolyte; and assembling 120 of the assembly of the electrochemical cell into a pouch cell, a cylindrical cell, or a prismatic cell. The assembly of the electrochemical cell typically includes an anode (active material and current collector), a cathode (active material and current collector), a separator, an electrolyte, and a housing in the form of a pouch, a cylindrical, or a prismatic package.
[0078] According to another aspect of this disclosure, a method for manufacturing a battery pack or module is provided. Reference is now made to... Figure 8 The method 150 typically includes the following steps: providing 155 plurality of electrochemical cells formed as pouch cells, cylindrical cells, or prismatic cells; providing a housing 160; connecting the electrochemical cells in parallel or in series 170; and placing the connected electrochemical cells 175 within the housing surrounding the pouch cells, cylindrical cells, or prismatic cells.
[0079] Those skilled in the art will understand from this disclosure that many changes can be made to the specific embodiments disclosed herein without departing from the spirit or scope of this disclosure and still obtaining the same or similar results. Those skilled in the art will also understand that any properties reported herein represent properties of conventional measurements and can be obtained by a variety of different methods. The methods described herein represent one such method, and other methods can be used without departing from the scope of this disclosure.
[0080] The foregoing description of various forms of the invention has been presented for purposes of illustration and description. It is not intended to be exhaustive or to limit the invention to the precise forms disclosed. In view of the foregoing teachings, many modifications or variations are possible. The forms discussed have been chosen and described to provide the best illustration of the principles of the invention and its practical application, thereby enabling those skilled in the art to utilize the invention in various forms and with various modifications suitable for the particular intended use. All such modifications and variations are within the scope of the invention as determined when the appended claims are interpreted in accordance with the breadth to which they should be enjoyed fairly, legally, and justly.
Claims
1. An electrochemical cell for converting chemical energy into electrical energy, said electrochemical cell being formed as a pouch cell, a cylindrical cell, or a prismatic cell; The electrochemical cell includes a coating material on one or more surfaces within the bag-shaped cell, cylindrical cell, or prismatic cell that are in contact with the electrolyte. The coating material comprises metal oxides and / or metal hydroxides and metal phosphates, such that the coating material is configured to reduce the amount of gas present within the electrochemical cell.
2. The electrochemical cell according to claim 1, wherein the coating material is located on the surface of the separator or current collector.
3. The electrochemical cell according to any one of claims 1 or 2, wherein the coating material comprises a homogeneous mixture of the metal oxide and / or metal hydroxide and the metal phosphate, or exists as a composite structure comprising the metal oxide and / or metal hydroxide in a first layer and the metal phosphate in a second layer.
4. The electrochemical cell according to claim 3, wherein the first layer comprises a first side and a second side, the first side being in direct contact with one or more surfaces within the bag-shaped cell, cylindrical cell, or prismatic cell, and the second layer being in direct contact with the second side of the first layer.
5. The electrochemical cell according to claim 3, wherein the homogeneous mixture is located within a single coating or within multiple coatings.
6. The electrochemical cell according to any one of claims 1 to 5, wherein the electrochemical cell is a metal battery or a metal-ion battery.
7. The electrochemical cell according to claim 6, wherein the metal battery or metal-ion battery is doped with one or more metals selected from lithium, sodium, potassium, magnesium, calcium or aluminum.
8. The electrochemical cell according to any one of claims 1 to 7, wherein the electrochemical cell is a lithium battery or a lithium-ion battery.
9. The electrochemical cell according to any one of claims 1 to 8, wherein the metal oxide or metal hydroxide includes aluminum oxide, aluminum hydroxide with the chemical formula AlOOH, zeolite, titanate, zirconate, aluminate, or a mixture or derivative thereof.
10. The electrochemical cell of claim 9, wherein the zeolite comprises a structure described as FAU, LTA, CHA, BEA or ZSM-5.
11. The electrochemical battery cell according to any one of claims 1 to 10, wherein the metal phosphate comprises amorphous aluminum phosphate, crystalline aluminum phosphate, aluminum phosphate molecular sieve, or a mixture thereof.
12. The electrochemical cell according to any one of claims 1 to 11, wherein the metal phosphate comprises a metal selected from the group consisting of Li, Mg, Ca, Sr, Ba, Ti, Zr and mixtures thereof.
13. The electrochemical cell according to any one of claims 1 to 12, wherein the coating material comprises the metal oxide or metal hydroxide and the metal phosphate in a mass ratio of 99:1 to 1:
99.
14. The electrochemical cell according to any one of claims 1 to 13, wherein the coating material comprises the metal oxide or metal hydroxide and the metal phosphate in a mass ratio of 90:10 to 10:
90.
15. The electrochemical cell according to any one of claims 1 to 13, wherein the coating material comprises the metal oxide or metal hydroxide and the metal phosphate in a mass ratio of 75:25 to 25:
75.
16. The electrochemical cell according to any one of claims 1 to 13, wherein, relative to the total mass of the coating material, the coating material comprises 99% to 25% by mass of the metal oxide or metal hydroxide and 1% to 75% by mass of the metal phosphate.
17. The electrochemical cell of claim 16, wherein, relative to the total mass of the coating material, the coating material comprises 98% to 50% by mass of the metal oxide or metal hydroxide and 2% to 50% by mass of the metal phosphate.
18. The electrochemical cell of claim 17, wherein, relative to the total mass of the coating material, the coating material comprises 95% to 75% by mass of the metal oxide or metal hydroxide and 5% to 25% by mass of the metal phosphate.
19. The electrochemical cell according to any one of claims 1 to 18, wherein the coating material further comprises a polymer binder at a mass percentage of 1% to 20% relative to the total mass of the coating material.
20. The electrochemical cell according to any one of claims 1 to 19, wherein the metal oxide or metal hydroxide is boehmite, and the metal phosphate is aluminum phosphate.
21. A battery pack or module comprising two or more electrochemical cells according to any one of claims 1 to 20 connected in series or in parallel with each other.
22. A method for preparing an electrochemical cell formed as a pouch cell, a cylindrical cell, or a prismatic cell according to any one of claims 1 to 21, wherein the method comprises the following steps: Components for the electrochemical cell are provided, including an anode, a cathode, a separator, an electrolyte, and a housing in the form of a bag, a cylinder, or a prismatic package; A coating material comprising metal oxides and / or metal hydroxides and metal phosphates is provided, such that the coating material is configured to reduce the amount of gas inside the battery cell; The coating material is applied to one or more surfaces located within the electrochemical cell that are in contact with the electrolyte; and The components of the electrochemical cell are assembled to form a pouch cell, a cylindrical cell, or a prismatic cell.
23. A method for manufacturing a battery pack or module, the method comprising the following steps: Provide two or more electrochemical cells formed by the method according to claim 22; Provide housing; Connect the two or more electrochemical cells in parallel or in series; The connected electrochemical cells are placed inside the housing, such that the housing surrounds the pouch-shaped cell, cylindrical cell, or prismatic cell to form the battery pack or module.
24. A coated spacer for forming an electrochemical cell as a pouch cell, a cylindrical cell, or a prismatic cell, the coated spacer comprising at least one layer of a porous polymer and at least one layer of a coating material comprising a metal oxide and / or a metal hydroxide and a metal phosphate, such that the coating material is configured to reduce the amount of gas generated when the coated spacer is used inside the electrochemical cell together with an organic electrolyte.
